Analyses of acute kidney injury biomarkers by ultra‐high performance liquid chromatography with mass spectrometry. Issue 1 (9th November 2015) - Za'abi, Mohammed Al; Ali, Badreldin H.; ALOthman, Zeid A.; Ali, Imran
Abstract : The newly developed acute kidney injury biomarkers are very important for the early and timely detection of kidney diseases. This review contains details of the analyses of several acute kidney injury biomarkers using ultra‐high performance liquid chromatography‐mass spectrometry in urine and plasma samples. In this review we attempt to discuss some aspects of the types of the biomarkers, patents, sample preparation, and the analyses. Besides, efforts were also made to discuss the possible uses of superficially porous (core–shell) columns in traditional and inexpensive high‐performance liquid chromatography instruments. Additionally, the challenges and the future prospects are also highlighted. The present review will be useful for the academicians, scientists, and clinicians for the early detection of acute kidney injury biomarkers.